How Well Do Employees Know Their Health Savings Accounts? The Need for Improved HSA Communication and Literacy - Perrault, Evan K. (Compensation and benefits review, 2025)
Health Savings Accounts (HSAs) have been around for two decades, with record funds accruing in accounts year-after-year. Despite this growth, little is known regarding how well consumers know what they can spend their HSA funds on to maximize their accounts’ tax advantages. A survey of HSA savers at a large Midwest organization (n = 732) found that about 1-in-4 employees (29.1%) were unsure or did not know their HSA contributions were not federally taxed. Additionally, employees knew that fewer than half of items asked about (M = 4.71) on a 10-item HSA-eligible quiz could be purchased with HSA funds. Employees had the least awareness that hand sanitizer (22.5%), sunscreen (27.2%), and menstrual care products (33.1%) could be purchased with HSA funds. Knowledge or perceptions did not differ based on employee education level, indicating that HSAs are likely a complicated topic for anyone to fully comprehend. These findings showcase a need to develop more effective communication to help employees better understand the unique benefits HSAs can provide. Additional recommendations for employers are provided.